2002
DOI: 10.1046/j.1365-2826.2002.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurosecretory and Non‐Neurosecretory Parvocellular Neurones of the Hypothalamic Paraventricular Nucleus Express Distinct Electrophysiological Properties

Abstract: Parvocellular neurones of the hypothalamic paraventricular nucleus (PVN) comprise neurosecretory and non-neurosecretory subpopulations. We labelled neurosecretory neurones with intravenous injection of the retrograde tracer, fluoro-gold, and recorded from fluoro-gold-positive and negative PVN parvocellular neurones in hypothalamic slices. Non-neurosecretory parvocellular neurones generated a low-threshold spike (LTS) and robust T-type Ca2+ current, whereas neurosecretory neurones showed no LTS and a small T-cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
125
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(139 citation statements)
references
References 8 publications
13
125
1
Order By: Relevance
“…First, as described previously (Luther and Tasker, 2000;Stern, 2001;Luther et al, 2002), after a hyperpolarizing current step, a 10 mV depolarization compared with resting membrane potential was evoked by current injection. In the lean silent group, we were able to evoke firing in three of the eight recorded neurons with an average frequency of 8.6 Ϯ 0.7 Hz (range: 7.52-10.07 Hz), whereas the rest of the neurons remained silent.…”
Section: Be)mentioning
confidence: 99%
See 4 more Smart Citations
“…First, as described previously (Luther and Tasker, 2000;Stern, 2001;Luther et al, 2002), after a hyperpolarizing current step, a 10 mV depolarization compared with resting membrane potential was evoked by current injection. In the lean silent group, we were able to evoke firing in three of the eight recorded neurons with an average frequency of 8.6 Ϯ 0.7 Hz (range: 7.52-10.07 Hz), whereas the rest of the neurons remained silent.…”
Section: Be)mentioning
confidence: 99%
“…Preautonomic PVN neurons regulate the sympathetic and parasympathetic tone through sympathetic neurons in the spinal cord and parasympathetic brainstem neurons, respectively (Rogers and Nelson, 1984;Yamashita et al, 1984;Lawrence and Pittman, 1985). Increased sympathetic activity was shown in the db/db mouse model (Rahmouni et al, 2003), which could contribute to elevated hepatic glucose production reported in db/db mice (Zhang et al, 2013). Because modulation of the synaptic balance and/or altering postsynaptic properties of liver-related PVN neurons is likely one of the underlying mechanisms of increased sympathetic activity, determining the cellular properties of liver-related PVN neurons is crucial to the understanding of the brain-liver circuit.…”
Section: Preautonomic Pvn Neurons and Liver Functionmentioning
confidence: 99%
See 3 more Smart Citations